Perioperative Darmprotektion - Weismüller, Katja; Hofer, Stefan; Weigand, Markus A. (Der Anaesthesist, 2012)
The gastrointestinal tract is a complex organ system. Dysfunctions of this organ system may evoke a variety of consequences for the entire organism and influence the inflammatory response in particular. In perioperative medicine, nutrition, prokinetics, peridural anesthesia, catecholamines and volume therapy can be applied in order to improve the gastrointestinal functional or at least to avoid further aggravation. Early enteral nutrition is especially important in the reduction of postsurgical ileus and infectious complications. Also, prokinetics and thoracic peridural anesthesia favorably affect postsurgical ileus. Norepinephrine, if necessary in combination with dobutamine, seems to have fewer negative effects on splanchnic perfusion than epinephrine. The data on volume therapy remain controversial but fluid balance has to be calculated very carefully also considering enteral loss of fluids. Thus, in order to treat and avoid gastrointestinal problems after surgery and to prevent negative effects for the complete organism, multimodal concepts with regard to detail are required.
Gesehen am 08.05.2019